2017
DOI: 10.3847/1538-4357/835/1/45
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Fermi-2lac Blazars to Diffuse Tev–pev Neutrino Flux

Abstract: The recent discovery of a diffuse cosmic neutrino flux extending up to PeV energies raises the question of which astrophysical sources generate this signal. Blazars are one class of extragalactic sources which may produce such high-energy neutrinos. We present a likelihood analysis searching for cumulative neutrino emission from blazars in the 2nd Fermi-LAT AGN catalog (2LAC) using IceCube neutrino data set 2009-12, which was optimized for the detection of individual sources. In contrast to those in previous s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
196
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 254 publications
(217 citation statements)
references
References 64 publications
14
196
0
1
Order By: Relevance
“…An interesting question concerns the potential contribution of the entire BL Lac population to the diffuse neutrino emission detected by IceCube (Aartsen et al 2017). In principle, BL Lac objects and FSRQs could account for a sizable fraction of the observed intensity (Tavecchio et al 2014;Righi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting question concerns the potential contribution of the entire BL Lac population to the diffuse neutrino emission detected by IceCube (Aartsen et al 2017). In principle, BL Lac objects and FSRQs could account for a sizable fraction of the observed intensity (Tavecchio et al 2014;Righi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several extragalactic candidates have been shown to have a sub-dominant contribution to the flux. Notably, blazars are constrained to contribute less than 27% of the flux for -E 2.5 or 50% if the spectrum is as hard as -E 2.2 (Aartsen et al 2017). Prompt emission from triggered gamma-ray bursts are strongly constrained to <1% contribution to the astrophysical flux (Aartsen et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…While the astrophysical neutrino flux has been detected in multiple channels with high significance, neither clustering in space or time nor cross correlations to catalogs have been found (Aartsen et al 2017a). The once promising sources for highenergy neutrinos such as GRBs (Abbasi et al 2012;Aartsen et al 2015e, 2017b and blazars (Aartsen et al 2017c) have been disfavored as the major contributors to the observed flux. To date, the origin of the astrophysical neutrinos remains a mystery.…”
Section: Introductionmentioning
confidence: 99%